THE EFFECT OF MONETARY POLICY ON ECONOMIC STABILITY IN INDONESIA: A LITERATURE REVIEW - Yogi Nurfauzi; Sunanto, Erna Handayani; Al-Amin (JOURNAL OF COMMUNITY DEDICATION, 2023)
Monetary policy plays a vital role in ensuring the stability of the economic system in Indonesia, where Bank Indonesia as the monetary authority has the main responsibility in setting interest rates and controlling the amount of money in circulation. The determination of interest rates by Bank Indonesia has a direct impact on consumption and investment activities. A decrease in interest rates generally encourages an increase in consumption and investment, which in turn can boost economic growth. However, interest rates that are too low over a long period of time may increase the risk of excessive inflation and financial system instability, as they may encourage excessive risk-taking by financial institutions and economic actors. Conversely, an overly tight monetary policy, with high interest rates, can hamper economic growth and increase unemployment, as high borrowing costs reduce consumption and investment spending. Firms may experience difficulties in financing operations and expansion, while consumers will be more cautious in their spending and investment. Therefore, it is important for Bank Indonesia to implement a balanced and flexible monetary policy, which is responsive to current economic conditions and various economic indicators. This balance in monetary policy is needed to ensure price stability, sustainable economic growth, and public welfare. Effective regulation and strict enforcement of supervision are also key in avoiding the negative impact of monetary policy that is either too loose or too tight. In conclusion, appropriate and measured monetary policy is an important instrument to achieve sustainable and inclusive stability of the Indonesian economic system.